Impact of fatty liver index and metabolic dysfunction-associated steatotic liver disease on the risk of benign prostatic hyperplasia in older male adults - Fan Zhang; Wenjian Li (BMC Geriatrics)
Abstract Objective The objective of this study was to ascertain whether the fatty liver index (FLI) and metabolic dysfunction-associated steatotic liver disease (MASLD) are independent risk factors for benign prostatic hyperplasia (BPH) in older men, and to evaluate their clinical utility in risk stratification. Methods The data utilized in this study were obtained from the National Health and Nutrition Examination Survey. After meticulous screening, 1,875 older male participants were included in the analysis. The relationships between FLI, MASLD, and BPH were examined by constructing multivariable logistic regression models, with the potential confounding variables considered. Furthermore, the dose-response relationships between FLI and BPH were investigated using restricted cubic spline curve (RCS) modeling, and subgroup analyses were conducted further to assess the differences in these relationships across populations. Results The findings revealed a statistically significant positive correlation between FLI and BPH, controlling for potential confounding variables. Furthermore, the risk of BPH increased markedly with increasing quartiles of FLI. Additionally, patients with MASLD exhibited a markedly elevated risk of BPH compared to non-MASLD participants. Furthermore, RCS analysis corroborated the linear positive association between FLI and BPH. Conclusion FLI and MASLD may be valuable tools for BPH risk assessment and contribute to the development of new prevention and treatment strategies. Clinical trial number Not applicable.